Pulchrin A, a New Natural Coumarin Derivative of Enicosanthellum pulchrum, Induces Apoptosis in Ovarian Cancer Cells via Intrinsic Pathway - Noraziah Nordin; Mehran Fadaeinasab; Syam Mohan; Najihah Mohd Hashim; Rozana Othman; Hamed Karimian; Venus Iman; Noorlela Ramli; Hapipah Mohd Ali; Nazia Abdul Majid (Public Library of Science, 2024)
Drug resistance presents a challenge in chemotherapy and has attracted research interest worldwide and particular attention has been given to natural compounds to overcome this difficulty. Pulchrin A, a new compound isolated from natural products has demonstrated novel potential for development as a drug. The identification of pulchrin A was conducted using several spectroscopic techniques such as nuclear magnetic resonance, liquid chromatography mass spectrometer, infrared and ultraviolet spectrometry. The cytotoxicity effects on CAOV-3 cells indicates that pulchrin A is more active than cisplatin, which has an IC50 of 22.3 ?M. Significant changes in cell morphology were present, such as cell membrane blebbing and formation of apoptotic bodies. The involvement of phosphatidylserine (PS) in apoptosis was confirmed by Annexin V-FITC after a 24 h treatment. Apoptosis was activated through the intrinsic pathway by activation of procaspases 3 and 9 as well as cleaved caspases 3 and 9 and ended at the executioner pathway, with the occurrence of DNA laddering. Apoptosis was further confirmed via gene and protein expression levels, in which Bcl-2 protein was down-regulated and Bax protein was up-regulated. Furthermore, the CAOV-3 cell cycle was disrupted at the G0/G1 phase, leading to apoptosis. Molecular modeling of Bcl-2 proteins demonstrated a high- binding affinity, which inhibited the function of Bcl-2 proteins and led to cell death. Results of the current study can shed light on the development of new therapeutic agents, particularly, human ovarian cancer treatments.